Limiting hauling ability and laws of friction of extensible flexible bodies in belt drive. Part 2 / V.I. Pozhbelko // Problems of Tribology. – 2012. – № 1. – Р. 95-105. - Пожбелко, В.И. (Problems of Tribology, 2014)
The paper contents determine the analytical dependences of hauling characteristics of elastic belt drive and define new universal friction constants of flexible bodies, which completely coordinate to experience and exactly define limits of rational design of friction mechanisms and flexible bodies friction theory improvement.